2022
DOI: 10.3390/ijms23073540
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of Systemic Therapy Investigations for Bone Sarcomas

Abstract: Bone sarcoma is a rare component of malignant solid tumors that accounts for only ~0.2% of malignancies. Bone sarcomas present various histological types, and genomic mutations differ markedly by the histological types. Although there are vast mutations in various bone sarcomas, most of them are non-actionable, and even potential targetable mutations that are actionable targets in other malignancies have not shown the appropriate responses in clinical trials for bone sarcomas. Investigations of new systemic th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 120 publications
(126 reference statements)
0
20
0
Order By: Relevance
“…So far, cisplatin based chemotherapy remains the pillar of major osteosarcoma patients. Unfortunately, some patients show prophase platinum resistance, relapse or disease progression after the initial treatment response [23]. Yang et al found that overexpression of Reptin in chemotherapy resistant ovarian cancer and breast cancer can improve DNA damage repair ability, and partially explained its resistance to treatment [24].…”
Section: Discussionmentioning
confidence: 99%
“…So far, cisplatin based chemotherapy remains the pillar of major osteosarcoma patients. Unfortunately, some patients show prophase platinum resistance, relapse or disease progression after the initial treatment response [23]. Yang et al found that overexpression of Reptin in chemotherapy resistant ovarian cancer and breast cancer can improve DNA damage repair ability, and partially explained its resistance to treatment [24].…”
Section: Discussionmentioning
confidence: 99%
“…Osteosarcoma (OS) is the most common primary malignant bone tumor, and represents the second leading cause of cancer-related death in children and adolescents [ 1 , 2 ]. Surgery combined with multimodal chemotherapy, comprising doxorubicin, methotrexate and cisplatin (CDDP), is the standard treatment for OS patients [ 3 , 4 ]. CDDP, an alkylating agent, functions in a cell-cycle-independent manner to cause DNA damage and cell death through alkylated DNA adducts [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sarcoma include both slow-growing tumors and highly malignant histological subtypes requiring a multimodal therapy regimen [ 2 , 3 ]. These interdisciplinary treatment concepts include surgery, radiotherapy, and systemic cancer therapy, as well as, in selected cases, regional hyperthermia [ 3 , 4 , 5 , 6 , 7 , 8 ]. In sarcoma, systemic chemotherapy-based treatment still plays a central role in patients with both curative and palliative disease [ 4 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In sarcoma, systemic chemotherapy-based treatment still plays a central role in patients with both curative and palliative disease [ 4 , 8 ]. Regarding the clinical data existing so far, anthracyclines alone or in combination with the alkylating agent ifosfamide are most commonly used [ 4 , 7 ]. Further treatment options such as trabectedin, eribulin, pazopanib, gemcitabine-based combinations, doxorubicin, cisplatin, etoposide, vincristine, and methotrexate depend on the primary histology, patient age, and comorbidities [ 7 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation